In situ investigation of degradation at organometal halide perovskite surfaces by X-ray photoelectron spectroscopy at realistic water vapour pressure. Issue 37 (26th April 2017) - Chun-Ren Ke, Jack; Walton, Alex S.; Lewis, David J.; Tedstone, Aleksander; O'Brien, Paul; Thomas, Andrew G.; Flavell, Wendy R.
Abstract : Near-ambient-pressure X-ray photoelectron spectroscopy enables the study of the reaction of in situ -prepared methylammonium lead iodide (MAPI) perovskite at realistic water vapour pressures for the first time. Abstract : Near-ambient-pressure X-ray photoelectron spectroscopy enables the study of the reaction of in situ -prepared methylammonium lead iodide (MAPI) perovskite at realistic water vapour pressures for the first time. We show that MAPI decomposes directly to PbI2, HI and NH3 without formation of methylammonium iodide, allowing us to distinguish between alternative mechanisms for the atmospheric degradation reaction.